The Role of Emotional Intelligence in Enhancing Employee Engagement Among Generation Z - Suyanto Suyanto; Rachmad Ilham; Adiba Fuad Syamlan (BADAN PENERBIT STIEPARI PRESS, 2025)
This study explores the role of emotional intelligence in enhancing employee engagement among Generation Z within the creative industry in Surabaya, Indonesia. As digital natives, Gen Z employees seek emotional connection, purpose driven work, and psychologically safe environments. Using a qualitative case study approach, data were collected through in depth, semi structured interviews with ten participants and analyzed using thematic analysis. The findings reveal three dominant themes: empathetic leadership fosters psychological safety, frequent emotional feedback strengthens interpersonal connections, and purpose driven roles enhance intrinsic motivation and engagement. These insights highlight the generational uniqueness of Gen Z and suggest that emotional intelligence is not only a personal asset but a strategic organizational capability. This study provides practical implications for leadership development, HR practices, and organizational culture aimed at improving engagement and retention among younger employees.